Combining high-flow nasal cannula oxygen therapy with repeated toilet bronchoscopies for respiratory failure due to excessive infected airway secretions: a case report and series from a non-intensive hospital ward - Fimognari, Filippo Luca; Baffa Bellucci, Francesco; Fedele, Flavio; Scarlata, Simone; Armentaro, Giuseppe; Sciacqua, Angela (Frontiers in Medicine, 2024)
Fiberoptic bronchoscopy (FBO) has diagnostic or therapeutic purposes, but can cause respiratory deterioration, particularly in patients with pre-existing acute respiratory failure (ARF). Noninvasive ventilation (NIV) and high flow nasal cannula oxygen therapy (HFNC) are used as respiratory support for ARF and also to prevent significant oxygen deterioration during FBO. The combined use of NIV and early therapeutic FBO to clear retained abundant infected secretions from the airways may be an alternative to intubation and invasive mechanical ventilation (IMV), but no data exists on the combined use of FBO and HFNC. A 78-year male patient with ARF secondary to chronic obstructive pulmonary disease (COPD) exacerbation and pneumonia was admitted to our non-intensive geriatric ward. After an initial improvement, his respiratory conditions worsened.While continuing HFNC, he was submitted to a series of 8 FBO during 9 days, each one performed in occasion of a significant decrease of peripheral oxygen saturation (SpO2 ) with the aim of removing copious and occlusive infected secretions from the airways, and always obtaining good SpO2 recovery. After etiological targeted antibiotic therapy based on bronchial aspirate, the patient improved and was discharged. Afterwards, 6 consecutive similar ARF patients were managed with the same strategy combining HFNC and repeated toilet FBO performed within the ward to clear secretions. All patients improved and were discharged. The combination of HFNC and repeated toilet FBO could be a safe and effective intervention to apply in non-intensive wards for preventing intubation and IMV in frail and elderly patients with ARF secondary to copious and occlusive infected secretions in the airways. 8. Scala R, Guidelli L. Clinical Value of Bronchoscopy in Acute Respiratory Failure.